2006
DOI: 10.1128/jb.00298-06
|View full text |Cite
|
Sign up to set email alerts
|

Functional Identification of Conjugation and Replication Regions of the Tetracycline Resistance Plasmid pCW3 fromClostridium perfringens

Abstract: Clostridium perfringens causes fatal human infections, such as gas gangrene, as well as gastrointestinal diseases in both humans and animals. Detailed molecular analysis of the tetracycline resistance plasmid pCW3 from C. perfringens has shown that it represents the prototype of a unique family of conjugative antibiotic resistance and virulence plasmids. We have identified the pCW3 replication region by deletion and transposon mutagenesis and showed that the essential rep gene encoded a basic protein with no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
247
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(253 citation statements)
references
References 56 publications
6
247
0
Order By: Relevance
“…Similarly, the netB-derived plasmids pJIR3536 and pNetB-NE10 share ϳ35 kb of conserved backbone (Fig. 2) with pCPF5603 and pCW3 (13,19,235,236). As mentioned above, some type E iota-toxin-encoding plasmids share substantial similarity with pCPF5603 (18), while others more closely resemble pCPF4969 (23).…”
Section: Plasmid Diversitymentioning
confidence: 98%
See 4 more Smart Citations
“…Similarly, the netB-derived plasmids pJIR3536 and pNetB-NE10 share ϳ35 kb of conserved backbone (Fig. 2) with pCPF5603 and pCW3 (13,19,235,236). As mentioned above, some type E iota-toxin-encoding plasmids share substantial similarity with pCPF5603 (18), while others more closely resemble pCPF4969 (23).…”
Section: Plasmid Diversitymentioning
confidence: 98%
“…All conjugative C. perfringens plasmids identified to date have the tcp locus, which has been demonstrated to be essential for conjugative transfer of pCW3 (236,(242)(243)(244)(245). Furthermore, either sequence analysis (13,14,23) or Southern hybridization analysis (14)(15)(16)(17)(18) indicated that many C. perfringens type B to E strains contain multiple large plasmids carrying toxin genes (cpb, etx, iapA/iapB, cpb2, and tpeL) and a tcp locus, which we assume is a reasonable predictor of their conjugative potential.…”
Section: Conjugative Transfer Of Toxin Plasmidsmentioning
confidence: 99%
See 3 more Smart Citations